Recommended diagnosis and management of atopic eczema. Issue 22 (19th November 2013) - MacKenzie, Andrew; Schofield, Olivia
Abstract The pathogenesis of atopic eczema is complex and its management requires a holistic approach. Our Drug review discusses its diagnosis, complications and the available treatment options, followed by sources of further information and an analysis of the prescription data.